Relationship of moulding pressure and weigh of granulate in improving the mechanical and characteristics of biopolymer from renewable resources - Abd Ghani, Mohd Khairul Zaimy (2016)
Waste cooking oils are problematic disposal especially in the developed countries. Options for disposing of waste cooking oil are limited. Pouring waste cooking oil down to the drain or sewers leads to clog and odour as well as damage wastewater leading to problems for humanlife. Thus, in this research, vegetable waste cooking oil is used as raw material to produce foam. This foam was crosslink with flexible isocyanate type Polymethane Polyphenyl (Modify polymeric-MDI) and further processed into granulate (powder) to be able to hot compress by hot compression moulding technique. These fabricated samples were namely as biopolymer. The conversion process of bio-monomer into BP was examined using Fourier Transform Infra-Red (FTiR) show the complete conversion of BP from bio-monomer indicated by 3351 cm-1 of N-H and carbonyls C=O functional groups at 1743 cm-1. Meanwhile the weight loss of BP as a function of temperature was determined by using Linseis Thermal Analyser (STA) (TG + DTA) indicating 3 distinct regions comprises of soft and hard segment degradation region at 253 °C and 410 °C respectively. The moulding pressure of 31 bar to 44 bar was set with different weight of granulate of BP from 110 gm to 160 gm. The compressed BP gives the highest tensile and flexural value of 4.89 MPa and 18.08 MPa respectively. Evidently, both compress BP of the highest tensile and flexural were affected by the highest density of 1.42 g/cm3. In general, the higher the compression moulding pressure the less void was examined, as well as the weight of granulates in the mould. The Scanning Electron Microscope (SEM) of fracture morphology surface of BP shows both ductile and brittle modes, and experiencing a ductile to brittle transition. This is due to increase interfacial strength at higher moulding pressure with good interfacial adhesion between granulates. Thus, the optimal combination of compression moulding parameters is helpful for polymer manufacturing with better mechanical properties such as tensile and flexural strength.